The Relationship Between Grit and Work Engagement Among Employees - Berliannda Nur Masithah; Diah Sofiah; Etik Darul Muslikah (Takaza Innovatix Labs Ltd., 2026)
This study aims to analyze the relationship between grit and work engagement among employees at PT X. Work engagement. Work engagement is a condition often experienced by employees characterized by a sense of enthusiasm and considering the work done to be very important. This study uses a quantitative approach with a correlational design and involves 113 employees of PT X as participants, through data collection using a Likert scale-based questionnaire that includes two main variables, namely: Grit and Work engagement. The results of the normality test of the distribution of the Grit scale with Work engagement against the One-Sample Kolmogorov Smirnov Test obtained a sig 0.071 at p = (p>0.05) which can be interpreted that the Grit scale with Work engagement is normally distributed. Based on the analysis of the hypothesis test using product moment correlation produces an rxy score of 0.343 with a significance value of 0.000 (p<0.01), which indicates a significant positive relationship between the grit variable and work engagement in employees so that the proposed hypothesis is accepted, meaning that the higher the Grit the higher the Work engagement